Humic substance application improves haematological indices of dog’s patients with myxomatous mitral valve disease - V. V. Rimskyi; V. S. Nedzvetsky (Theoretical and Applied Veterinary Medicine, 2024)
Endocardiosis of the mitral valve is one of the most common heart diseases in small breed dogs. The first clinical symptoms, namely cough and inability to bear exercise, appear 3-4 years after the first damage to the valvular apparatus. Symptoms of a stagnant heart failure are due to the presence of regurgitation, which over time leads to an increase in the volume of the left atrium and, as a result, an increase in blood pressure in the pulmonary veins. Due to hypoxia and damage to the myocardium, a significant amount of reactive oxygen species and inflammatory markers are released into the blood, which negatively affect the processes of lipid peroxidation, which leads to a deterioration of the body's antioxidant protection. The results of present study have shown the changes in clinical blood analysis indices for mitral valve endocarditis when adding humic substances to the main protocol of therapy. For research, we selected 12 dogs with mitral valve endocardiosis in stage C according to the classification of the American College of Veterinary Internal Medicine (ACVIM). Confirmation of the pathology was carried out with the use of echocardiography together with complex diagnostics. The animals were conditionally divided into 2 experimental (ST and ST+H) and 1 control group. In addition to the standard therapy of this disease, the drug "Humilid 1%" was added to the diet of the ST+H group during 21 day at the proportion of 10 mg/kg of the active substance once a day. Blood was collected from animals of all groups at the beginning and on the 21st day of the study. The results of clinical blood analysis showed that the addition of substances based on humic compounds to standard therapy increases the total number of erythrocytes in the circulating peripheral blood by 8% and increases the level of haemoglobin and haematocrit by 10.8% and 1.8% (р > 0.05) respectively. The total level of platelets in the ST group significantly increased by 23% (p < 0.04), although in the ST+H group, on the contrary, it decreased by 7% (p > 0.05), but it did not exceed the reference norms in neither group. During the 21 days of the study, the total level of leukocytes did not change in all groups. In the ST+H group, it was found that the absolute number of monocytes was higher than the reference values of 0.9 ± 0.3 109/L on the first day of the study and significantly decreased to 0.4 ± 0.2 109/L (р > 0.05) on the 21st day of administering of “Humilid 1%". Positive changes in leukocyte indices were also detected, which indicates the positive effect of humic compounds on reducing the aseptic inflammatory process, as a complication of mitral valve endocardiosis. In the future, it is planned to study the effect of humic substances on the antioxidant/prooxidant balance of the dog, as well as to study their expected protective potential on the functioning of internal organs affected with myxomatous degeneration of the mitral valve.